Physical and physiological characteristics of high-level combat sport athletes - Tabben, M.; Chaouachi, A.; Hedi Mahfoudhi, M.; Aloui, A.; Habacha, H.; Tourny, C.; Franchini, E. (Journal of Combat Sports and Martial Arts, 2014)
Background. This study attempted to establish physical and physiological characteristics of different high-level combat sport athletes (judo, karate, and taekwondo) and to determine possible differences between these athletes. Material and methods. Fifty-four elite judo (n = 19), karate (n = 19) and taekwondo (n = 16) athletes took part in the present study. The experimental design consisted of two test sessions. On the first one, athletes performed the squat jump (SJ), countermovement jump (CMJ), and a maximal treadmill test to determine O 2max . The second session included the five jump test (5JT), 30m sprint, and one repetition-maximum (1RM) during three exercises: bench-press, half-squat and lying row. Results. The results showed that SJ and CMJ heights and 5JT performances were higher in karate athletes than in judo and taekwondo athletes. Conversely, bench-press, half-squat and lying row 1RM were higher in judo athletes compared to karate and taekwondo athletes. However, no significant difference was found in O 2max and 30-m sprint between groups. Conclusion. These results can be used for athlete selection in the different combat sports.